'Experimental investigation of the effect of ambient gas temperature on the autoignition properties of ethanol–diesel fuel blends'. (15th February 2018) - Kuszewski, Hubert
Highlights: Ignition and combustion delay for ethanol–diesel fuel blends were measured. Tests of the autoignition were conducted for different ambient gas temperatures. During investigation, the constant volume combustion chamber was used. Abstract: Due to increasing fuel consumption in various industries, especially in road transport, interest in increasing the market proportion of renewable fuels is growing. The raw materials for production of ethanol may include sugar beets, sugar cane, potatoes and many other plants containing starch. In some countries, ethanol has been successfully used for many years as a self-contained fuel in positive-ignition engines after subjection to relatively minor technical modifications. Due, among other things, to a very low cetane number, this fuel cannot be used in diesel engines. For this reason, increasing attention is being paid to fuels that are blends of diesel with some ethanol fraction. Diesel fuel containing up to 15% (v/v) of ethanol is sometimes referred to as e-diesel or oxygenated diesel. In this study, the autoignition properties of blends of typical diesel fuel with ethanol have been tested with ethanol contents up to 14% (v/v) and where a constant volume combustion chamber was used. The study determined the effect of gaseous medium temperature in the range 550–650 °C on the period of ignition delay and the period of combustion delay. The average and maximum rates of pressure rise in the combustion chamber were also analysed. Studies have shown that, with an increase of ethanol fraction in diesel fuel, the periods of ignition and combustion delay increase, and the increase in the temperature of the gaseous medium into which the fuel is injected shortens these periods to a varying extent.